How to write and give a speech a practical guide for executive, PR people, managers, fundraisers pliticians, educators, and anyone who has to make every word count. - Detz, Joan (New York St. Martin's Press, 1984)
Contents: Common difficulties of businessmen and professionals in public speaking. Planning ideas. Work with words. Connect with the audience. Manage your visuals. Business presentations. Special concerns. Sample speeches. Index.
Purpose: "It is an invaluable guide for everyone of us who has a message to convey, and wants to convey it with effectiveness and conviction; and it uses humor and anecdotes to emphasize points on how we can all be effective public speakers."
Keywords: Public speaking